2021
DOI: 10.1108/ajems-03-2021-0101
|View full text |Cite
|
Sign up to set email alerts
|

Financial literacy, financial distress and socioeconomic characteristics of individuals in Ghana

Abstract: PurposePersonal financial stress-free living is desired by many, which dwells on sound financial literacy (including financial behaviour, financial knowledge and financial attitude). Many individuals do not make optimal savings and investment decisions. The realisation that these choices may well lead to low living standards has also increased economic anxiety, especially in Sub-Sahara African countries, including Ghana. Thus, this study underscores the link between financial literacy and financial distress in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 47 publications
(54 reference statements)
0
12
0
Order By: Relevance
“…Financial knowledge is crucial in today's society as it affects every aspect of life, such as student loans, mortgages, credit cards, savings and health insurance (Klapper & Lusardi, 2020). Research has shown that having financial knowledge enables an individual to be more prepared for particular financial roadblocks, which reduces the likelihood of experiencing personal financial distress (Karakara et al, 2021). Financial knowledge has a significant and consistent role in financial decision-making (Karakara et al, 2021), as well as in transforming financial beliefs (such as financial attitude and perceived behavioural control) and behavioural intentions into behaviours (Popovich et al, 2020).…”
Section: Financial Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…Financial knowledge is crucial in today's society as it affects every aspect of life, such as student loans, mortgages, credit cards, savings and health insurance (Klapper & Lusardi, 2020). Research has shown that having financial knowledge enables an individual to be more prepared for particular financial roadblocks, which reduces the likelihood of experiencing personal financial distress (Karakara et al, 2021). Financial knowledge has a significant and consistent role in financial decision-making (Karakara et al, 2021), as well as in transforming financial beliefs (such as financial attitude and perceived behavioural control) and behavioural intentions into behaviours (Popovich et al, 2020).…”
Section: Financial Knowledgementioning
confidence: 99%
“…Research has shown that having financial knowledge enables an individual to be more prepared for particular financial roadblocks, which reduces the likelihood of experiencing personal financial distress (Karakara et al, 2021). Financial knowledge has a significant and consistent role in financial decision-making (Karakara et al, 2021), as well as in transforming financial beliefs (such as financial attitude and perceived behavioural control) and behavioural intentions into behaviours (Popovich et al, 2020). Financial knowledge enhances people's financial behaviour by increasing their confidence in managing their finances (Radianto et al, 2021).…”
Section: Financial Knowledgementioning
confidence: 99%
“…This applies especially to the condition of the Indonesian people, whose financial literacy remains low relative to the Asia-Pacific region (Harahap et al , 2022). Financial literacy can be defined as a person’s knowledge and skills regarding their financial attitudes and behaviour when making financial decisions (Karakara et al , 2022). Understanding financial literacy can provide benefits, such as being able to prepare financial plans and understand financial products to determine the most appropriate (Liu et al , 2023).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Social protection describes a country's policy framework that consists of public actions taken in response to levels of vulnerability, risk, poverty and deprivation. It deals with both the vulnerabilities of the extreme poor and with the security of the nonpoor in the presence of hazards (Karakara et al, 2021). Social program like cash transfers and farm inputs subsidy, particularly among smallscale farmers, are mostly done in rural and poverty-driven communities.…”
Section: Introductionmentioning
confidence: 99%
“…Social protection describes a country's policy framework that consists of public actions taken in response to levels of vulnerability, risk, poverty and deprivation. It deals with both the vulnerabilities of the extreme poor and with the security of the nonpoor in the presence of hazards (Karakara et al. , 2021).…”
Section: Introductionmentioning
confidence: 99%